Tradition and innovation in biblical interpretation: studies presented to professor Eep Talstra on the occasion of his sixty-fifth birthday - Peursen, Willem Th. van; Talstra, Eep (Studia Semitica Neerlandica, 2011)
PART ONE: TRADITION AND INNOVATION IN THE BIBLE ITSELF -- A story of three prophets: synchronic and diachronic analysis of Jeremiah 26 / Joep Dubbink -- 'Against you, daughter of Bablyon!': a remarkable example of text-reception in the oracle of Jeremiah 50-51 / Eric Peels -- 'Reading Jeremiah makes me angry': the role of Jeremiah 32[39]:36-41 in transformation within the 'Jeremianic' tradition / Janneke Stegeman -- Beyond 'singers and syntax': theological and canonical reflections on Psalm 8 / Carl J. Bosma -- Where is God: Romans 3: 13-18 as an addition to Psalm 14 / Eveline van Staalduine-Sulman -- Reading Qohelet as text, author, and reader / Timothy Walton -- Tradition through reading-reading the tradition: reflections on Eep Talstra's exegetical methodology / Louis Jonker -- PART TWO: TRADITION AND INNOVATION IN THE RECEPTION OF THE BIBLE -- Between stigmatizing and idolizing the Bible: on the reception of Genesis 12: 10-20; 20; 26: 1-11 / Cornelis Houtman -- 'Out of Egypt I have called my son': Matthew 2: 15 and Hosea 11: 1 in Dutch and American Evangelical interpretation / Gert Kwakkel -- Daniel's four kingdoms in the Syriac tradition / Wido van Peursen -- The identity of Israel's God: the potential of the so-called extra-Calvinisticum / Cornelis van der Kooi -- A Jewish childbirth amulet from the Bibliotheca Rosenthaliana / Margaretha Folmer -- PART THREE: TRADITION AND INNOVATION IN LINGUISTIC AND COMPUTATIONAL APPROACHES TO THE BIBLE -- Computer-assisted tools for textual criticism / Emanuel Tov -- On Biblical Hebrew and computer science: inspiration, models, tools, and cross-fertilization / Ulrik Sandborg-Petersen -- Persuasive Hebrew exercises: the wit of technology-enhanced language learning / Nicolai Winther-Nielsen -- Judging Jephthah: the contribution of syntactic analysis to the interpretation of Judges 11: 29-40 / Klaas Spronk -- Masoretic tradition and syntactic analysis of the Psalms / Luis Vegas Montaner -- Who is speaking-who is listening? How information technology can confirm the integrity of the text / Oliver Glanz -- Jerusalem's comforters in Isaiah 40:1-2: participant tracking in a prophetic text / Reinoud Oosting -- Hebrew hāyāh: etymology, bleaching , and discourse structure / Frank Polak -- The Lexeme [...] / Christo H.J. van der Merwe -- Language, structure, and strategy in Isaiah 53: 1-6: [...], word order, and the translator / Lénart J. de Regt -- [...] in Job 34: 36 / Constantine J. Sikkel -- Dissertations under the guidance of Eep Talstra -- Publications by Eep Talstra -- Index of sources Index of modern authors